Pemanfaat Literasi Digital dalam Pengembangan UMKM di Wilayah Cikarageman: Pengabdian - Herawati, Heny; Lestari, Sri; Bandawaty, Euis; Suldina, Farida; Sanjoyo; Siddiq, Achmad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The rapid advancement of technology in the digital era has significantly simplified business operations. However, not all entrepreneurs possess adequate understanding and skills to optimally utilize digital technology in their business processes. This condition highlights the importance of enhancing digital literacy among business actors, particularly in the areas of business management and marketing. In response to this need, the Management Study Program of the Faculty of Economics, Universitas Islam As-Syafi’iyah conducted a digital literacy training program for 20 housewives and MSME entrepreneurs in Cikarageman Village, Setu District, East Bekasi. The program aimed to facilitate participants’ transformation from conventional business practices to digitally based systems. The training focused on implementing digital marketing strategies through the use of social media and the Shopee marketplace platform. Participants were trained to create engaging promotional content, such as photos, videos, and persuasive copywriting, to attract online consumers. The results of the activity showed that participants were able to understand and directly apply digital media utilization in their business activities. This improvement positively affected marketing effectiveness, market reach expansion, and potential income growth through more systematic financial management.